Desain dan Analisa Tegangan Tarik Maksimum Dan Tegangan Tekan Maksimum Kait (Hook) Pada Overhead Crane - Rahman. R, Laode; Gunawan, Yuspian; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2021)
In the industrial world there have been many innovations and creations aimed at improving the quality and quantity of production. In industrial and construction activities, there are usually material or material loads that cannot be lifted using human power. For industry, there is a lifting device called a crane. Cranes have a main component called a hook which is used to help lift the load by being hooked. Hooks that are designed incorrectly will be dangerous when used, so it is necessary to check the stress through theoretical analysis calculations or by simulation using Autodesk Inventor to evaluate the construction through the safety factor and Von Misses stress analysis so that the construction made on the hook does not experience failure. The results of theoretical analysis and simulation results using Autodesk Inventor 2017 software on a hook with a load of 3 Tons or 29.430 N can be concluded that the maximum compressive stress of cross section AB is 5.19 kg/ mm2 tensile stress of cross section AB is 15.40 kg/mm2 and on the CD cross section the maximum compressive stress is 4.97 kg/mm2 and the maximum tensile stress is 13.35 kg/mm2, the safety factor based on simulation is 15. It can be concluded that, the Hook which has been analyzed theoretically and simulation can be said to be able to accept a load of 3 tons.Keywords: Hook, overhead crane